Characteristics of Pedagogical Technologies. Modular Technology - Elmuradova Laylo Normuratovna (Research Parks Publishers, 2021)
Modular training is a method of structuring the educational process based on the presentation of educational information in a block-modular manner. Modular learning has a long history as an educational tool. The article describes its history, structures, differentiation from other techniques, ways to develop a training module and all its aspects.